Oral health problems in high-performance athletes at 2019 Pan American Games in Lima: a descriptive study - Catalina Opazo-García; Jeel Moya-Salazar; Karina Chicoma-Flores; Hans Contreras-Pulache (Nature Publishing Group, 2021)
Abstract Introduction Dental care is provided for high-performance athletes at national and international sports events. Elite athletes may seek care for sports-related injuries and pre-existing oral diseases. Previous studies indicate an association between oral health problems and negative performance impacts in elite athletes. Objectives To determine the prevalence of the most common oral pathologies in high-performance athletes during the emergency dental care performed at the Lima 2019 Pan American Games (JPL-19). Methodology All reports of athletes (≥18 years old, of both sexes, from 41 countries) who received emergency dental care at Pan American Villas during the JPL-19 were included. Injuries and types of oral diseases were classified according to the Injury and Disease Surveillance System proposed by the International Olympic Committee. Results Of the 6680 participating athletes, 76 (1.14%) presented as dental emergencies, 90.8% (69/76) of the athletes seen presented pre-existing oral pathological conditions, the most frequent were periodontal diseases (34%, 26/76) and dental caries (29%, 22/76). Among the sports with the most cases, there were 22 (29%) in athletics, 6 (8%) in soccer, and 6 (8%) in taekwondo. The most frequent dental emergencies came from Peru, Puerto Rico, Bahamas, Grenada, and Venezuela. Conclusions Pre-existing oral diseases were more frequent than sports-related accidents. The most prevalent diseases were periodontal disease and dental caries disease. It is necessary to implement new care strategies for athletes, based on prevention, before and during sports competitions.